Utilizing Cobit 4.1 and Balance Scorecard to Manage Information Technology Business Process in Higher Education Institution - Eriana, Emi Sita; Susanti, Leni (Journal of Social Science and Business Studies, 2024)
Pamulang University's Information Technology Strategy Plan aims to develop a comprehensive strategy to maximize IT efficiency and effectiveness in the institution. Using the COBIT 4.1 approach, SWOT analysis, and Balanced Scorecard, this plan identifies strengths, weaknesses, opportunities, and threats in the current IT infrastructure and develops an integrated strategy for IT development. COBIT 4.1 provides a framework for managing and controlling IT by ensuring that IT processes support business objectives and meet stakeholder needs. The SWOT analysis explores the internal and external factors that influence IT at Pamulang University, while the Balanced Scorecard helps in establishing balanced strategic metrics and objectives across multiple perspectives, including financial, customer, internal processes, and learning and growth. This strategic plan is expected to improve IT management, support the achievement of Pamulang University's goals and facilitate data-based decisions for innovation and continuous improvement.